Blends of PVDF and a conducting polymer - Nogueira, J. S.; Malmonge, L. F. [UNESP]; Mattoso, L. H.C. (Institute of Electrical and Electronics Engineers (IEEE), 1994)
Blends of poly(vinylidene fluoride)-PVDF and-poly(o-methoxyaniline)-POMA-of various compositions were produced by casting in dimethylformamide (DMF). Flexible films were obtained which were characterized, using scanning electron microscopy, X-ray diffraction, two-probe conductivity, dielectric polarization, thermo-stimulated current (TSC) and differential scanning calorimetry (DSC). As expected, the blends conductivity increases considerably with increasing contents of doped POMA. These polymer blends possess conductivity in a wide range what may be seen as a new class of semiconductors. The influence of the conducting polymer on the characteristics of PVDF is discussed.